One, none, a hundred thousand metaverses - Bory, Paolo; Negro, Gianluigi (Funes. Journal of narratives and social sciences, 2025)
The announcement of the metaverse is quite a unique case in digital media history. Unlike previous product launches, the metaverse was introduced not as a stabilized medium or platform but as a promissory assemblage: a future socio-technical system made of interoperable “worlds” and grounded in new and more exciting interactions during working and leisure activities. This issue of Funes illustrates the contested imaginaries of the metaverse, oscillating between Zuckerberg’s utopia (or dystopia) and a complete failure, which confirms the need for a symmetrical and more nuanced approach in analysing such phenomena. The metaverse imaginaries are already contributing to the present and future of MR and will likely give rise to unexpected practices and new forms of “worldings”, yet to be discovered, but not to be left unexplored in the making.